Wheeled Robot Control with a Bluetooth-Based Smartphone - Iswanto Suwarno; Nia Maharani Raharja (Journal of Telecommunication Control and Intelligent System, 2021)
A wheeled robot is a robot that can walk on a flat surface with the help of wheels as its driving medium, this wheeled robot is made using Arduino as a programming brain, where this robot can move forward, backward, turn right and turn left with a smartphone via a bluetooth module, This wheeled robot is controlled via a smartphone as the remote control and the Bluetooth HC-05 as a connecting medium between the smartphone and the robot. In addition to using Arduino, this robot uses an l298n motor driver as an output regulator for DC motors. From the results of testing on this design it can be concluded that the speed of the experimental robot I was 0.58 m/s for a distance of 3 meters can be completed in 5.1 seconds, in experiment II with 0.56 m/s with the same distance and for 5.3 seconds, and in experiment III it can be completed in 5.5 seconds with a speed of 5.4 m/s, the difference in speed and duration between experiments is influenced by factors such as reduced robot battery voltage and the process of sending data and pairing can be done as far as 13 meters.